Manajemen Rantai Pasok Pada PT. Fastfood Indonesia (KFC) Di Kota Batam - A Alvin; Illianto Tri Sagianto; Adeline Oktalia; Gelasia Gwyneth; Fandion Melsen; Novi Sandra; Vanessa Flesya; Julia Christini (Jurnal TUNAS, 2022)
In the journal that we will be working on, the aim is to understand how supply chain management is on the supply of raw materials in the food and beverage industry, especially in international franchise companies. This study uses qualitative research techniques. The data that has been collected will be analyzed using steps that are often called triangulation, namely: Data reduction; Data Display Factors of supply chain management that impact raw material inventory, and conclusions. In qualitative research, the population and samples taken are called informants. Supply chain management has an impact on the supply of sufficient and quality raw materials, if supply chain management is good it will make inventory always maintained and can meet needs and demands when needed. KFC must always improve the governance or management of the company's supply chain so that raw materials are always sufficient and always available whenever needed. The supply chain is very important and influential so that KFC can sell its products with sufficient and quality raw materials so that consumers get good products. If consumers get a quality product, they are likely to buy it again and invite their closest people to try it.